Keefektifan Problem Based Learning terhadap Kemampuan Berpikir Kritis - Muhammad Aunur Rofiq (Nusa Putra University, 2019)
Critical thinking skills is something very important for children. In social studies, there are material need critical thinking. Pretest in class V SDN Todanan 1, found the critical thinking capability is low. Result of preliminary studies it is known that 44,8% or 13 students have not reached the minimum completeness criteria was currently working in in the form of critical thinking test. The purpose this research is analyze result of studies between control class and experiment class, and analyze the effectiveness PBL for increase student’s result studies. Research design use quasi experimental design type nonequivalent control group design. There are two kinds instrument of this research. The instrument is implementatios of learning instrument and data collection instrument. Data collection method used is critical thinking test. The effectiveness of learnning shown by students learning completeness reached 79% and independent samplet-test show students critical thinking abilities experimental class is better than control class. Critical thinking ability of students experimental class increased by 9,1. The conclusion from this research is that Problem Based Learning Model effective to student’s result social studies. Suggestions for other researchers was need for further research as the development of research in the another subject matter.